(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article explores the progress and prospects of alternative energy sources in Uzbekistan as the nation strives to reduce its reliance on fossil fuels and build a more sustainable energy future. Increasing attention is being directed toward renewable sources such as solar, wind, and hydropower. The study analyzes the current development of these energy sectors, evaluates relevant government policies, and considers the role of international cooperation. In addition, it identifies major challenges—including infrastructural limitations and financial constraints—that hinder rapid progress. The article emphasizes that sustained investment and innovation are essential to ensuring the successful transition of Uzbekistan’s energy system.